2016
DOI: 10.7705/biomedica.v36i2.2784
|View full text |Cite
|
Sign up to set email alerts
|

Factores de riesgo para bacteriemia adquirida en el hospital por Pseudomonas aeruginosa resistente a carbapenémicos en un hospital colombiano

Abstract: Contribución de los autores:Todos los autores participaron en el diseño del estudio, el análisis e interpretación de los resultados, y en la redacción y aprobación del manuscrito. Introducción. Las bacteriemias por Pseudomonas aeruginosa resistentes a carbapenémicos son un problema de salud pública por las pocas alternativas de tratamiento disponibles, el aumento de la estancia hospitalaria, los costos que genera y el aumento en el riesgo de mortalidad. Objetivo. Evaluar los factores de riesgo de bacteriemia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
4
0
9
Order By: Relevance
“…Our study also found an independent association between total parenteral nutrition and XDR-PA infections. Similar to previous findings, parenteral nutrition was shown to be associated with the acquisition of MDRPA [ 33 ] or bacteremia due to CRPA [ 34 ]. However, in contrast to previous findings, we found no association of either previous PA colonization or high APACHE II scores with XDR-PA infections [ 14 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our study also found an independent association between total parenteral nutrition and XDR-PA infections. Similar to previous findings, parenteral nutrition was shown to be associated with the acquisition of MDRPA [ 33 ] or bacteremia due to CRPA [ 34 ]. However, in contrast to previous findings, we found no association of either previous PA colonization or high APACHE II scores with XDR-PA infections [ 14 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 86%
“…found no correlations between the presence of class I integron and MDR in clinical P. aeruginosa strains. Other studies have shown that P. aeruginosa isolates from patients with a history of long antimicrobial treatment developed MDR/XDR; long hospital stay and readmission to the Intensive Care Unit were associated with MDR in patients with bacteremia caused by this species 41 , 42 .…”
Section: Discussionmentioning
confidence: 97%
“…8 Although transmission of resistant strains and also the spread of resistance via plasmids are not refuted by this current study, these data were based on prefectural units and the mode of spread was not separately captured from the dataset. Similarly, the use of medical devices including intravenous catheters 6,911 was not captured in this current study’s dataset, and if such datasets were collected at greater resolution (e.g. by hospital or by hospital ward), associations between these risk factors and P. aeruginosa resistance in Japan could be analysed.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Epidemiological studies have identified several risk factors for carbapenem-resistant P. aeruginosa infection including use of medical devices, such as artificial respirators and central intravenous catheters, and admission to an intensive care unit with carbapenem use. 6,911…”
Section: Introductionmentioning
confidence: 99%